PENGARUH PENGGUNAAN WEB PHET SIMULATION DALAM ROOM FRACTION TERHADAP KEMAMPUAN BERHITUNG PESERTA DIDIK SEKOLAH DASAR - Putri, Auliya; Khairani, Fadhilah; Profithasari, Nindy; Yulistia, Annisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low ability to calculate fractional material worth of students in mathematics subjects at SDN 1 Tanjungan is the problem of this research. The purpose of this study was to determine the influence of PhET simulation media on the ability to calculate fractional material in grade IV elementary school. This study used a type of quantitative research quasi experiment method with a non-equivalent control group design. The research sample consisted of 48 students who were selected through purposive sampling techniques from a total population of 77 students. The data collection technique used test instruments in the form of description questions and non-tests in the form of observation sheets. Data analysis was carried out by simple linear regression test. The results of a simple linear regression test showed that PhET simulation media had an effect on the ability to calculate fractional material worth of grade IV students by 74.9%.